Pengaruh Kompres Dingin Dan Myofacial Release Terhadap Penurunan Nyeri Akibat Cedera Otot Pada Ekstrakurikuler Tapak Suci - Fadhli Azmi Susilo; Virgianti Nur Faridah; Rizky Asta Pramestirini (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Objective: Muscle injuries are among the most common occurrences in the Tapak Suci extracurricular program, whether during training sessions or competitive events. If left untreated, such injuries can disrupt daily activities, necessitating interventions like cold compress therapy and myofascial release to manage pain effectively. This study aims to examine the effect of cold compress therapy and myofascial release on pain reduction in members of the Tapak Suci extracurricular program at Al-Mizan Muhammadiyah Islamic Boarding School, Lamongan. Methods: An analytic correlational study with a cross-sectional approach was employed. The sample consisted of 117 nurses selected through cluster random sampling. Data were collected using questionnaires and analyzed using the Spearman rho test via SPSS software. Results: The results indicate a significant effect of cold compress therapy and myofascial release on pain reduction. demonstrating the effectiveness of these interventions in alleviating muscle pain. Conclusion: Members of the Tapak Suci extracurricular program are encouraged to learn and apply these therapeutic techniques for future injury management. Additionally, further studies should compare different therapeutic interventions across groups to enhance understanding of optimal pain management strategies.